Self Disclosure of College Students who use Instagram Second Account Based on Interpersonal Trust: Self Disclosure Mahasiswi Pengguna Second Account Instagram Berdasarkan Interpersonal Trust - Maharani, Furi Dhenisa; Wibowo , Danan Satriyo; Widyarini , Nurlaela (Psikologia : Jurnal Psikologi, 2025)
Second accounts are additional social media profiles used by individuals to share content separate from their primary accounts, typically comprising followers who are close acquaintances and mutually trust each other. Consequently, users of second accounts engage in self-disclosure, whereby they reveal personal information to their followers. The objective of this study is to examine the relationship between interpersonal trust and self-disclosure among female college students who use second accounts on Instagram. The research population consists of female students in Jember, with a sample size of 274 individuals selected through purposive sampling. The study employed the interpersonal trust scale adapted from Asmaini (2020) and the self-disclosure scale adapted from Arwa (2021). The findings reveal a significant positive correlation between interpersonal trust and self-disclosure (r=.490; p<.05), indicating that higher levels of interpersonal trust are associated with increased self-disclosure among female college students who use second accounts on Instagram. Students who trust their second account followers tend to feel comfortable and relatively more open in disclosing various aspects of themselves.Highlights: Trust fosters openness – Higher interpersonal trust leads to greater self-disclosure among second account users. Selective audience – Second accounts are primarily followed by close, trusted acquaintances. Significant correlation – Study confirms a strong positive relationship (r=.490; p<.05) between trust and self-disclosure. Keywords: Interpersonal Trust, Second Account Instagram, Self Disclosure